Postharvest conservation of strawberries from three new accessions cultivated in the south of Minas Gerais – Brazil (Research, Society and Development, 2022)
The objective of this work was to evaluate the postharvest conservation of fruits of three strawberry accessions (NP4, NP9, NP15) under two storage conditions, comparing them with the fruits of cv. Oso Grande (control treatment). The fruits, with 75% of their surface with red color, were harvested, selected and placed in PET containers with lid and stored under ambient conditions (20±3 °C and 81±7% relative humidity) and under refrigeration (5± 1 ºC and 90±4% relative humidity). During the 11 days of storage, the following evaluations were carried out: total soluble solids (TSS), total titratable acidity (TTA), TSS/TTA ratio, pH and the loss of mass of fruits kept under different storage conditions. Under environmental conditions, the maximum longevity of the fruits was three days and the best preservation was observed in the fruits of the NP9 strawberry tree. Under refrigeration, the longevity of the fruits extended until the 11th day, when the fruits of the NP9 and NP15 access strawberries exhibited better characteristics when compared to the fruits of NP4 and 'Oso Grande', thus representing a new option for growing fruits for consumption in natura for producers in southern Minas Gerais.